Baby skin care tips - E. S. Keshishyan; Е. S. Sakharova; N. V. Afanasyeva (Медицинский совет, 2018)
The article proposes a variant of functional responsibilities distribution between the patronage nurse and the doctor regarding counselling on the baby skin care and correction of the most frequent and typical disruptions of its continuity. It presents the main structural characteristics of the skin in young children. Theoretical justification of the differentiated approach to the choice of skin care products are provided.